Bioethical dimensions of old age - Lolas Stepke, Fernando (Acta Bioethica, 2001)
The increase of senior citizens in last decades and the greater longevity of the population will bring a high demand for services in the final stages of life. There is a close association between ageing-as a process that intersects what is biological, social and biographical-and death, that actually can not be separated from culture. Old age is a stage of loss and reduced capability. Not only at the visible level but also related to its performance, the biological body is no longer what it used to be and it undergoes a negative transformation. Along with the biological and biographical spheres, there is the social one, related to values. Crucially, ageing is the biographical stage evidenced by certain exterior attributes. According to the social clock of each community it has its own duties and rights. All behavioural normative becomes senseless if there is no freedom to accept or reject it. Only in such a context dialogue-which constitutes the very essence of social life-can be practiced. If lost, the own identity as a moral agent or as an autonomous person gets damaged. The ethics of quality of life in old age must be founded and grounded on moderate, modest, and factible expectations. Dialogue is the most important tool with which bioethical discourse has contributed to modern societies. Even though medicine is a basic social metaphor, care and social insertion procedures should include a special sensibility towards relationships of power, the contexts wherein human relations are interpreted, and the cultural facts that influence the treatment of the elderly.